Adaptation of Agile Spotify Model at the Government Digital Service - Rizki Wijaya; Wahyudi Kumorotomo; Ratminto; Achmad Djunaedi (Polit Journal Scientific Journal of Politics, 2024)
Jabar Digital Service (JDS) took an innovative approach by smoothly integrating Spotify's agile model into the government's structure. This transformation went beyond simple structural changes. It completely reconfigured bureaucratic structures to match the agile culture required for effective digital service delivery. JDS proactively adapted its organizational structure by recruiting highly skilled professionals to meet the specific needs of the digital environment. In addition, the organization implemented the Agile at Scale and Heterogeneous Tailoring frameworks. These frameworks increased independence and promoted consistency in decision-making, enabling a fundamental change in the way JDS delivered projects and introducing collaborative groups such as squads, tribes and divisions. This integration required a complete restructuring of cultural standards, regulatory systems, risk mitigation procedures and thorough staff development. The process of communicating effectively with team stakeholders and achieving a balance between team autonomy and alignment in a changed organization was challenging. A variety of methods were used to support this research, including an in-depth exploration and observation of JDS, semi-structured interviews with relevant staff, a comprehensive case study approach using holistic single case design, and a detailed analysis of previous research, regulations and secondary data sources. The impact of this pioneering project was far-reaching. It facilitated the establishment of digital signatures to simplify bureaucratic procedures, the conversion of analogue forms into digital domains, and the digitalization of business activities. The development of JDS was an important milestone in the digital transformation process, as it facilitated collaboration between the community and the government on digital services. Significantly, this undertaking used Spotify's operational framework, adapting and customizing it to the specific needs and difficulties of JDS, which represents a notable advance in government digital integration